2022
DOI: 10.3390/pathogens11060626
|View full text |Cite
|
Sign up to set email alerts
|

Digital Marketing: A Unique Multidisciplinary Approach towards the Elimination of Viral Hepatitis

Abstract: New technologies are supported by the global implementation of the internet. These improvements have deeply affected various disciplines of sciences and consequently changed services such as daily business, particularly health sectors. Innovative digital marketing strategies utilize the channels of social media and retrieved user data to analyze and improve relevant services. These multidisciplinary innovations can assist specialists, physicians and researchers in diagnostic, prophylaxis and treatment issues i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 233 publications
0
7
0
1
Order By: Relevance
“…According to Nunan and Di Domenico ( 10 ), Purcarea ( 11 ), Purwanto ( 12 ), and Pourkarim et al ( 13 ), digital marketing effects and barriers are something to manage during COVID-19. A digital marketing strategy is adopted to manage work online and persist with safety precautions.…”
Section: Discussion and Opinionmentioning
confidence: 99%
“…According to Nunan and Di Domenico ( 10 ), Purcarea ( 11 ), Purwanto ( 12 ), and Pourkarim et al ( 13 ), digital marketing effects and barriers are something to manage during COVID-19. A digital marketing strategy is adopted to manage work online and persist with safety precautions.…”
Section: Discussion and Opinionmentioning
confidence: 99%
“…For instance, a positive impact has been achieved by influencers (vloggers) campaigning for hygienic behavior in the context of COVID-19 and other infections. 8 At the same time, negative consequences of vlogger activities have also been reported due to the dissemination of videos on idealistic body image and unhealthy food, causing body image dissatisfaction and anxiety among adolescents and other vulnerable subjects. 9 Overall, surveys of public views have concluded that health news dissemination via social media may have mixed, positive and negative consequences, the latter due to lack of critical expert evaluations, desperate information-seeking behavior of some public representatives, and inability to distinguish scientific facts from misinformation by non-expert users.…”
mentioning
confidence: 99%
“…Recent estimations show that almost two-thirds of the world's HBsAg-positive children (below 5 years) inhabit Africa [6]. Together with the lack of access to screening tests for pregnant women and weak public knowledge about the risk factors of viral hepatitis infection, these limitations can have serious consequences for the viral hepatitis burden in this region [7].…”
mentioning
confidence: 99%